Kajian Teoritis Implementasi Peer-Assessment untuk Meningkatkan Kemampuan Partisipasi Peserta Didik pada Pembelajaran Kooperatif - Adawiyah, Siti Rabiatul (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2022)
The curriculum currently applied in Indonesia, namely Curriculum 2013 demands that learning be directed at student-centered-learning, so that the teacher is no longer the only actor in the learning process but shifts to become a facilitator. One of the learning models that involve students actively in the learning process is the cooperative learning model. However, in its implementation it often causes problems, namely the occurrence of gaps in student participation in group work. This participation gap will lead to new problems, especially if the teacher gives the same value to all group members without considering the contribution of each student. Meanwhile, to assess the performance of each student in the group, it is not easy for the teacher to do this, especially if the number of students is quite large in one class. One solution to overcome these problems is to implement peer-assessment. This study aims to provide a theoretical study of the application of peer-assessment to increase student participation in cooperative learning. This research is a library research (library research). Researchers obtain data by conducting literature reviews from various sources such as books, journals, scientific works, as well as documents and other relevant literature.